LEARNERS’ CULTURAL BACKGROUND AND ENGLISH AS A FOREIGN LANGUAGE LEARNING IN A PESANTREN-BASED UNIVERSITY: A PRELIMINARY STUDY - Adib, Muhammad Najib Al (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Learners' cultural background is a significant thing in learning English where they are expected to be able to adapt to the new language. The community of teachers and learners with pesantren backgrounds has unique characteristics different from the world of native English speakers. This research studies EFL learners' background of pesantren-based students in Universitas Sains Al Qur’an Wonosobo. It covers three issues, i.e. the way learners adapt their cultural background and experiences to English language learning, the way learners’ cultural background is involved in the English language acquisition process, and the way learners’ cultural conceptualization in their first language acquisition contributes to English language learning. Twenty English learners agreed to participate in the research. Adopting a qualitative design, the results highlighted that these learners have been able to make cultural adjustments from initially being Islamic boarding school students to becoming English language course students, students with their santri identity can make adjustments and sort out cultures that do not match their self-identity, they also felt that they preferred to gain knowledge about cultural concepts different from those they experienced in the pesantren. This research is important to support the consideration of curriculum and material development in Teaching English to students of Islamic schools, especially in intercultural language instruction.